Composite powder for use in negative electrode of battery and battery comprising such composite powder

By using composite powder containing carbon matrix material and embedded silicon-based particles in the negative electrode of the lithium-ion battery, the problem of difficulty in achieving high capacity and long cycle life in the prior art is solved, and efficient battery performance and service life are achieved.

CN119731119AActive Publication Date: 2025-03-28UMICORE(BE)
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202380063644.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-20
Filing Date
2023-09-18
Publication Date
2025-03-28
Estimated Expiration
2043-09-18

AI Technical Summary

Technical Problem

The prior art is difficult to achieve both high capacity and long cycle life in the negative electrode of lithium-ion batteries, especially for electric vehicles.

Method used

Using a composite powder containing a carbon matrix material and silicon-based particles embedded therein, the structure and performance of the composite powder is controlled by the ID/ID' ratio of Raman spectroscopy to achieve a combination of high capacity and long cycle life.

Benefits of technology

The high capacity and long cycle life of the negative electrode of the lithium-ion battery are achieved, and the overall performance and service life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119731119A_ABST
    Figure CN119731119A_ABST
Patent Text Reader

Abstract

A composite powder for use in a negative electrode of a battery, the composite powder comprising composite particles comprising a carbon matrix material and silicon-based particles embedded in the carbon matrix material, the composite powder having a Raman spectrum, wherein the D band and the D'band, both corresponding to the contribution of the carbon matrix material, have a maximum intensity ID between 1330 cm <-1 > and 1360 cm <-1 > and a maximum intensity ID 'between 1600 cm <-1 > and 1620 cm <-1 >, respectively, with the ratio ID / ID' being at least equal to 0.9 and at most equal to 4.0.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Technical Field and Background Art

[0002] The present invention relates to composite powders suitable for use in negative electrodes of batteries and batteries comprising such composite powders.

[0003] Lithium-ion (Li-ion) batteries are currently the best performing batteries and have become the standard for portable electronic devices. In addition, these batteries are rapidly gaining popularity in other industries such as automotive and electrical storage. The advantageous advantage of these batteries is the combination of high energy density with good power performance.

[0004] Li-ion batteries usually contain a plurality of so-called Li-ion cells, which in turn contain a positive electrode (also called cathode), a negative electrode (also called anode) and a separator immersed in an electrolyte. The most common Li-ion batteries for portable applications were developed using electrochemically active materials such as lithium cobalt oxide or lithium cobalt nickel manganese oxide for the cathode and natural or artificial graphite for the anode.

[0005] It is known that one of the important limiting factors affecting battery performance and in particular battery energy density is the active material in the anode. Therefore, in order to increase the energy density, the use of electrochemically active materials containing silicon in the negative electrode has been studied in the past few years.

[0006] In the art, the performance of batteries containing Si-based electrochemically active powders is generally quantified by the so-called cycle life of the full cell, which is defined as the number of times or cycles that a battery containing such materials can be charged and discharged before reaching 70% of its initial discharge capacity. Therefore, most work on silicon-based electrochemically active powders has focused on improving said cycle life.

[0007] A disadvantage of using silicon-based electrochemically active materials in the anode is their large volume expansion during charging, which can be as high as 300% when lithium ions are fully incorporated into the active material of the anode (e.g., by alloying or intercalation), a process generally referred to as lithiation. The large volume expansion of silicon-based materials during lithium incorporation can induce stresses in the silicon-based particles, which in turn can lead to mechanical degradation of the silicon material. Due to the repeated cycles during charge and discharge of Li-ion batteries, the repeated mechanical degradation of silicon-based electrochemically active materials can shorten the battery's life to unacceptable levels.

[0008] In addition, a negative effect associated with silicon is the possible formation of a thick SEI (solid electrolyte interface) on the anode. SEI is a complex reaction product of electrolyte and lithium, which leads to the loss of lithium that can participate in electrochemical reactions and thus leads to poor cycle performance, that is, capacity loss per charge-discharge cycle. Thick SEI can further increase the resistance of the battery, thereby limiting its ability to charge and discharge at high currents.

[0009] In principle, SEI formation is a self-terminating process that stops once a "passivation layer" forms on the surface of the silicon-based material. However, due to the volume expansion of the silicon-based particles, both the silicon-based particles and the SEI may be damaged during discharge (lithiation) and recharge (delithiation), thereby releasing new silicon surfaces and causing new SEI formation to begin.

[0010] In order to solve the above-mentioned disadvantages, composite powders are usually used. In these composite powders, nano-scale silicon-based particles are mixed with at least one component suitable for protecting the silicon-based particles from electrolyte decomposition and accommodating volume changes. Such components can be carbon-based materials, preferably forming a matrix.

[0011] The composite powders usually additionally contain graphite particles in order to adjust their specific capacity to a practical level, which is between 500 and 1500 mAh / g.

[0012] For example, such composite powders are mentioned in US 2019 / 0198863, which discloses an anode active material comprising a composite of a Si-based or Sn-based material and a carbon-based material, wherein the D peak (1360 cm -1 Up to 1370cm -1 ) peak intensity (I D ) relative to the D' peak (1620 cm -1 Up to 1625cm -1 ) peak intensity (I D' ) of the Raman spectrum peak intensity ratio (I D / I D' ) is 4.5 to 10.

[0013] GB 2563455 discloses a granular material composed of a plurality of composite particles, wherein the composite particles comprise a plurality of silicon nanoparticles dispersed in a conductive carbon matrix, wherein the contribution of the conductive carbon matrix in the Raman spectrum of the granular material is characterized by a large G band and a significant D band. GB 2563455 does not mention the existence of the D' band, nor does it mention the intensity ratio of the D band and the D' band, respectively. D / I D' Related technical effects.

[0014] WO 2022074031 discloses a powder of carbon-containing matrix material particles, in which silicon-based subparticles are dispersed. WO 2022074031 does not disclose any Raman data.

[0015] EP 3113261 discloses a negative electrode material for a non-aqueous electrolyte secondary battery, comprising a conductive powder consisting of silicon-based active material particles coated with a conductive carbon film, wherein the conductive carbon film exhibits a peak intensity ratio l of 1.1 or less.D / l G , where l D is the peak intensity of the D band, l G is the peak intensity of the G band, and the D band and the G band are determined by the Raman spectrum of the conductive carbon film. EP 3113261 does not mention the existence of the D' band, nor does it mention the intensity ratio I to the D band and the D' band, respectively. D / I D' Related technical effects.

[0016] WO 2010 / 065739 discloses an article comprising a carbon-containing matrix having a Raman spectrum with up to 4 bands, namely at about 1360 cm -1 (D belt), about 1580cm -1 (G belt), about 1620cm -1 (D' band) and about 2660cm -1 WO2010 / 065739 does not mention the intensity ratios I to the D band and D' band, respectively. D / I D' The related technical effects are also not mentioned for silicon-based particles embedded in a carbon-containing matrix.

[0017] Despite the use of such composite powders, there is still room for improvement in the performance of batteries containing Si-based electrochemically active powders. In particular, existing composite powders do not allow high capacity and long cycle life to be achieved simultaneously, which is essential, in particular, for batteries for electric vehicles.

[0018] The object of the present invention is to provide a composite powder comprising composite particles comprising a carbon matrix material and silicon-based particles embedded therein, which composite powder, once used in a negative electrode of a battery, is advantageous in that it allows a combination of high capacity and long cycle life to be achieved. Summary of the invention

[0019] This object is achieved by providing a composite powder according to the invention which, once used in the negative electrode of a battery, allows a combination of high capacity and long cycle life to be achieved, as demonstrated by Examples 1 to 3 compared with Counter Examples 1 to 3. DETAILED DESCRIPTION

[0020] In the following specific embodiments, preferred embodiments are described in detail to practice the present invention. Although the present invention is described with reference to these specific preferred embodiments, it should be understood that the present invention is not limited to these preferred embodiments. On the contrary, the present invention includes many alternatives, modifications and equivalent forms, which will become apparent by considering the following specific embodiments and the accompanying drawings.

[0021] In a first aspect, the present invention relates to a composite powder for use in a negative electrode of a secondary battery, the composite powder comprising composite particles, the composite particles comprising a carbon matrix material and silicon-based particles embedded in the carbon matrix material, the composite powder having a Raman spectrum obtained by Raman scattering, wherein a D band and a D' band both corresponding to contributions of the carbon matrix material have a peak at 1330 cm -1 With 1360cm -1 The maximum intensity between D and at 1600cm -1 With 1620cm -1 The maximum intensity between D' , where the ratio I D / I D' At least equal to 0.9 and at most equal to 4.0.

[0022] Maximum Intensity I D Preferably at 1330cm -1 With 1359cm -1 between 1330cm and 1330cm -1 With 1357cm -1 and even more preferably between 1330 cm -1 With 1355cm -1 Between, and the maximum intensity I D' Preferably at 1600cm -1 With 1619cm -1 between 1600cm and 2000cm, more preferably between 1600cm and 2000cm -1 With 1617cm -1 and even more preferably between 1600 cm -1 and 1615cm -1 between.

[0023] Preferably, the composite particles consist of a carbon matrix material and silicon-based particles embedded therein.

[0024] By "composite particles comprising a carbon matrix material and silicon-based particles embedded in the carbon matrix material" is meant that the average size of the composite particles is larger than that of the silicon-based particles because they comprise silicon-based particles. The composite particles are typically micrometer-sized, while the silicon-based particles are typically nanometer-sized.

[0025] The "silicon-based particles embedded in the carbon matrix material" means that at least 50% of the surface of the silicon-based particles is covered by the carbon-based material, preferably at least 75% of the surface of the silicon-based particles is covered by the carbon-based material, and preferably the silicon-based particles are completely covered by the carbon-based material to ensure proper prevention of reaction with the electrolyte during cycling. In other words, the silicon-based particles and the carbon matrix material are not simply mixed together, because this would not achieve proper coverage of the surface of the silicon-based particles.

[0026] The silicon-based particles embedded in the carbon matrix material either form agglomerates with a size of less than 1 μm or do not form agglomerates at all. Therefore, in the composite powder according to the invention, the silicon-based particles are preferably only in contact with each other and / or with the carbon matrix material.

[0027] The silicon-based particles may have any shape, for example substantially spherical, but may also have irregular shapes, rods, plates, etc. In the silicon-based particles, silicon is mainly present in the form of metallic silicon, to which small amounts of other elements may have been added to improve properties, or may contain some impurities such as oxygen or trace metals. When all elements except oxygen are taken into account, the average silicon content in such silicon-based particles is preferably 80% by weight or more, and more preferably 90% by weight or more, relative to the total weight of the silicon-based particles.

[0028] In the Raman spectrum of graphite materials such as the carbon matrix material of the composite powder according to the present invention, the most prominent feature is the so-called -1 The G band at about 1350cm -1 The D band at about 1610 cm -1 The D' band at about 2700 cm -1 The G' band (also called the 2D band) at . Figure 1 A graphic representation of a typical Raman spectrum of a graphite material with 4 distinct bands is shown.

[0029] The presence of the G band is characteristic of the in-plane vibrational modes involving sp2 hybridized carbon. The D and D' bands are defect-induced Raman features that are not seen for highly crystalline carbon materials with few defects. The intensity ratio of the D band to the G band is D / I G Often used to characterize the amount of defects in graphite materials.

[0030] However, within the framework of the present invention, the inventors have noticed that another intensity ratio (i.e., the I of the D band and the D' band) D / I D' ) and the performance of the battery, as presented elsewhere in this article.

[0031] The inventors believe that I D / I D' is a good indicator of defect concentration and its type, such as edge, vacancy type defects, boundary type defects or defects associated with changes in carbon hybridization, e.g. from sp 2 becomes sp 3 .

[0032] Ratio I D / I D'Above 4.0 is undesirable as this indicates that the defect concentration in the carbon matrix material is too high, which may, for example, be detrimental to the electronic conductivity of the composite particles. In addition, this may also indicate that the defects are of a "more destructive" type, such as those associated with sp 3 Those associated with hybridization, which are believed to be detrimental to the cycle life of the battery.

[0033] Ratio I D / I D' A value below 0.9 is also undesirable since it indicates that the defect concentration in the carbon matrix is ​​too low, which may be detrimental, for example, to the ionic conductivity of the composite particles.

[0034] In other words, with the ratio I D / I D' The associated technical effect reaches its maximum value between 0.9 and 4.0.

[0035] In another embodiment according to the first aspect of the present invention, the ratio I D / I D' Preferably it is at least equal to 1.0, more preferably at least equal to 1.2, even more preferably at least equal to 1.4, particularly preferably at least equal to 1.6, more particularly preferably at least equal to 1.8 and quite preferably at least equal to 2.0. D / I D' Preferably it is at most equal to 3.8, more preferably at most equal to 3.6, particularly preferably at most equal to 3.4, more particularly preferably at most equal to 3.2, and most preferably at most equal to 3.0. In other words, with the ratio I D / I D' The associated technical effect reaches its maximum value between 2.0 and 3.0.

[0036] In another embodiment according to the first aspect of the invention, the carbon matrix material is soft carbon. Soft carbon corresponds to an arrangement of small disordered graphite domains that can be converted to graphite when heated at a temperature of 3000°C, in contrast to non-graphitizable hard carbon.

[0037] Soft carbons show higher electronic conductivity than hard carbons and are therefore preferred. In addition, due to the disordered aggregation of small graphite domains, which results in the presence of nanovoids in the matrix material, particles comprising a matrix material comprising mainly soft carbon have reduced volume expansion during lithiation of the anode compared to particles comprising a matrix material comprising mainly graphite or graphene. Reduced volume expansion will extend the cycle life of the battery.

[0038] In another embodiment according to the first aspect of the invention, the composite powder has a silicon content S expressed as weight percent (wt %), wherein 10 wt % ≤ S ≤ 60 wt %, and preferably wherein 20 wt % ≤ S ≤ 50 wt %.

[0039] Composite powders with a silicon content below 10% by weight, preferably below 20% by weight, will have too limited a specific capacity and will therefore not allow a high energy density of the battery to be achieved. Composite powders with a silicon content above 60% by weight, preferably above 50% by weight, will suffer too much from the volume expansion associated with this high silicon content and will therefore lead to a shortened cycle life of the battery.

[0040] In yet another embodiment according to the first aspect of the present invention, the composite powder has a carbon content C expressed as weight percentage (wt %), wherein 30 wt % ≤ C ≤ 90 wt %.

[0041] When the carbon content in the composite powder is less than 30 wt %, the amount of carbon-containing matrix material present is insufficient to completely cover the silicon-based particles, resulting in increased electrolyte decomposition at the surface of the silicon-based particles and thus increased SEI formation. When the carbon content in the composite powder is greater than 90 wt %, the specific capacity of the composite powder is too low.

[0042] In another embodiment according to the first aspect of the invention, the composite powder has a silicon content S and an oxygen content N, both expressed in weight percent (wt %), wherein N≤0.20×S and preferably wherein N≤0.15×S.

[0043] Composite powders with too high an oxygen content will suffer additional irreversible lithium loss due to the formation of lithium silicates (Li2SiO3, Li4SiO4) during the first lithiation of the powder, thereby increasing the initial irreversible capacity loss of batteries containing such composite powders.

[0044] In another embodiment according to the first aspect of the present invention, the silicon-based particles are characterized by a size distribution based on number having a d50 greater than or equal to 20 nm and less than or equal to 150 nm.

[0045] The number-based size distribution is based on a visual analysis of a minimum number of silicon-based particles contained in the composite powder, with or without the aid of an image analysis program. This minimum number of silicon-based particles is at least 1000 particles. An example of determining a number-based distribution of silicon-based particles is provided in the "Analytical Methods" section.

[0046] For clarity, for example a d50 of 100 nm would here mean that 50% of at least 1000 silicon-based particles have a size smaller than 100 nm and 50% of at least 1000 silicon-based particles have a size larger than 100 nm.

[0047] Silicon-based particles with a number-based size distribution of d50 below 20 nm are difficult to disperse effectively in a carbon matrix material, which may reduce the electronic conductivity of the powder.

[0048] Silicon-based particles having a number-based size distribution with a d50 greater than 150 nm are more susceptible to breakage during lithiation, resulting in a significantly reduced cycle life of batteries containing such composite powders.

[0049] It is believed that the d50 is not affected by the process of preparing the composite powder, which means that the d50 value of the silicon-based powder used as a precursor in the process is the same as the d50 value of the silicon-based particles contained in the composite powder.

[0050] In another embodiment according to the first aspect of the invention, the surface of the silicon-based particles, for example at least 50%, preferably at least 75%, is covered by the carbon matrix material. Preferably, the silicon-based particles are completely covered by the carbon matrix material. This can be visually confirmed based on analysis of one or more SEM images of a cross-section of a composite powder comprising the silicon-based particles.

[0051] As already mentioned, a negative effect associated with silicon is the possible formation of a thick SEI (solid-electrolyte interface) on the anode, in particular on the silicon-based particles. Since the silicon-based particles are subject to large volume changes during the lithiation / delithiation process in the battery, the already formed SEI may break again, resulting in a continuous consumption of lithium and, thus, a significant reduction in the battery cycle life. At least partially protecting the surface of the silicon-based particles with a carbon matrix material is an effective solution to prevent continuous SEI formation and cycle life loss.

[0052] In another embodiment according to the first aspect of the invention, the silicon content in the silicon-based particles is at least equal to 80% by weight, and preferably at least equal to 90% by weight.

[0053] Preferably, these silicon-based particles do not contain other elements than Si and O, in order to avoid that the specific capacity of the silicon-based particles is too low. The silicon-based particles are the main contributor to the specific capacity of the composite powder, it is preferred that their own capacity is as high as possible, and therefore their silicon content is as high as possible, in this case at least 80% by weight and preferably at least 90% by weight.

[0054] In another embodiment according to the first aspect of the present invention, the composite powder also includes graphite and / or graphene particles, but graphite particles and graphene particles are not embedded in the carbon matrix material. So-called "graphite particles and graphene particles are not embedded in the carbon matrix material", refers to that less than 10% of the surface of graphite and / or graphene particles is covered by carbon matrix material, preferably less than 5% of the surface is covered by carbon matrix material, and more preferably their surface is not covered by carbon matrix material at all. This can be visually confirmed based on the analysis of one or more SEM images of the cross section of the composite powder. In fact, it is beneficial that graphite and / or graphene particles are not embedded in the matrix material, because only silicon-based particles need to be covered with carbon matrix material, so less carbon matrix material with high irreversible capacity and low specific capacity is needed.

[0055] However, there may be some contact between the composite particles and the graphite and / or graphene particles, which contact is at their outer surfaces. This is even preferred in order to ensure that the composite powder has good electronic conductivity and thus a battery comprising the composite powder has high rate capability.

[0056] In addition, the graphite particles act as spacers between the composite particles, thereby preventing these composite particles from agglomerating into agglomerated powders. In the absence of such spacers, the agglomerated powders may require mechanical treatments, such as a grinding step, for use in the negative electrode of a battery, which may lead to a weakening of the integrity of the matrix material and ultimately to reduced performance of batteries containing such agglomerated powders.

[0057] Alternatively, the composite powder may also contain exfoliated graphite, expanded graphite and / or graphene nanoplatelets, none of which are embedded in a matrix material for the same reasons as above.

[0058] Since these graphite materials may have an influence on the Raman spectrum of the composite powder, their contribution should be removed to obtain a ratio I having only the contribution of the carbon matrix material. D / I D' , in particular their contribution to the D and D' bands. The procedure is explained in more detail in the "Analytical methods" section.

[0059] In another embodiment according to the first aspect of the present invention, the composite powder has a maximum 2 / g and preferably at most 8m 2 / g of BET surface area.

[0060] Preferably, the composite powders have a low BET specific surface area to reduce the surface of the electrochemically active particles in contact with the electrolyte in order to limit the formation of a lithium-consuming SEI and thus limit the cycle life loss of batteries containing such composite powders.

[0061] In another embodiment according to the first aspect of the present invention, the composite particles have a volume-based particle size distribution including D10, D50 and D90, wherein 1 μm≤D10≤10 μm, 5 μm≤D50≤25 μm and 10 μm≤D90≤40 μm.

[0062] For the sake of clarity, for example, a D50 of 15 μm means that 50% by volume of the composite particles have a size smaller than 15 μm and 50% by volume of the composite particles have a size larger than 15 μm.

[0063] Matrix material particles having a volume-based size distribution with a D50 of less than 5 μm may have too high a specific surface area, thereby increasing the surface area for reaction with the electrolyte and the formation of SEI, which is unfavorable for the reasons explained previously. Matrix material particles having a volume-based size distribution with a D50 of greater than 25 μm may be more susceptible to crack formation during lithium absorption due to their size, resulting in a shortened cycle life of batteries containing such particles.

[0064] In a second aspect, the invention relates to a negative electrode for a battery, preferably a lithium-ion battery, comprising a composite powder according to the invention. The negative electrode generally also comprises a conductive additive, such as carbon black, graphite particles, graphene particles, carbon nanotubes or mixtures thereof. The content of the conductive additive is between 0% and 10% by weight, in particular 0.1% to 5% by weight, relative to the total weight of the negative electrode layer (excluding the current collector).

[0065] The negative electrode also typically contains a binder or a mixture of binders. Specific examples of binders include polysaccharides, lithium polyacrylate (Li-PAA), sodium polyacrylate (Na-PAA), potassium polyacrylate (K-PAA), polyacrylic acid (H-PAA), sodium carboxymethyl cellulose (Na-CMC), styrene-butadiene rubber (SBR). The binder is added to improve the cohesion of the various components of the negative electrode, its mechanical strength on the current collector, or even its flexibility. Relative to the total weight of the negative electrode layer (excluding the current collector), the binder accounts for 1 wt % to 15 wt %, in particular 2 wt % to 10 wt %. Examples of negative electrode preparation are provided elsewhere in this article.

[0066] Finally, the invention also relates to a battery, preferably a lithium-ion battery, comprising a negative electrode according to the invention and therefore a composite powder according to the invention, as defined previously or prepared as disclosed previously.

[0067] The battery according to the invention more particularly comprises a negative electrode (anode) according to the invention, a positive electrode (cathode) and an electrolyte, preferably a non-aqueous electrolyte. As examples of positive electrodes, mention may be made of a material selected from the group consisting of LiCoO2, LiNi 0,6 Mn0,2 Co 0,2 O2、LiNi 0,8 Mn 0,1 Co 0,1 O2、LiNi 0,8 Co 0,15 Al 0,05 O2、Li 1,2 Ni 0,2 Mn 0,6 O2, LiFePO4 and the like positive electrode active material. The electrolyte may preferably be a non-aqueous electrolyte solution, a non-aqueous polymer electrolyte or even a solid electrolyte. Specific examples thereof include organic electrolyte solutions obtained by dissolving lithium salts such as LiClO4, LiPF6, LiAsF6, LiBF4, LiSO3CF3, CH3SO3 Li, CF3SO3Li and the like in non-aqueous solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), propylene carbonate (PC), butylene carbonate, acetonitrile, propionitrile, dimethoxyethane, tetrahydrofuran, γ-butyrolactone and the like; gel polymer electrolytes containing polyethylene oxide, polyacrylonitrile, polyvinylidene fluoride, polymethyl methacrylate and the like; and solid polymer electrolytes containing polymers having ethylene oxide bonds. In addition, additives that cause decomposition reactions during the initial charging of the lithium ion battery may also be added to the electrolyte solution. Specific examples of the additive include vinylene carbonate (VC), biphenyl, propane sultone (PS), fluoroethylene carbonate (FEC), ethylene sultone (ES), etc. The amount added is preferably not less than 0.1 wt % and not more than 20 wt % relative to the total weight of the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS

[0068] Figure 1 :Graphite Raman spectrum diagram

[0069] Figure 2 : Raman spectrum of composite powder E1 with peak fitting

[0070] Analytical methods used

[0071] Determination of silicon content

[0072] The silicon content of the composite powders was measured by X-ray fluorescence (XRF) using energy dispersive spectroscopy. This method has an experimental random error of + / - 0.3 wt% Si.

[0073] Determination of oxygen content

[0074] The oxygen content of the composite powders was determined using a LECO TC600 oxygen and nitrogen analyzer by the following method. The powder sample to be analyzed is placed in a closed tin cuvette, which itself is placed in a nickel basket. The basket is then placed in a graphite crucible and heated to above 2000°C with helium as carrier gas. The sample thus melts and the oxygen reacts with the graphite in the crucible to produce CO or CO2 gas. These gases are directed to an infrared measuring cell. The observed signal is recalculated as the oxygen content.

[0075] Determination of carbon content

[0076] The carbon content of the composite powder was determined using a Leco CS230 carbon-sulfur analyzer by the following method. The sample was melted in a ceramic crucible in a high-frequency furnace in a constant oxygen flow. The carbon in the sample reacts with the oxygen and leaves the crucible as CO or CO2. After the final CO present is converted to CO2, all the CO2 produced is ultimately detected by an infrared detector. This signal is ultimately converted to carbon content.

[0077] Determination of specific surface area (BET)

[0078] The specific surface area of ​​the composite powders was measured using the Brunauer-Emmett-Teller (BET) method using a Micromeritics Tristar 3000. 2 g of the powder to be analyzed was first dried in an oven at 120 °C for 2 h and subsequently purged with N2. Then, before the measurement, the powder was degassed in vacuum at 120 °C for 1 h in order to remove adsorbed substances.

[0079] Determination of electrochemical properties

[0080] The electrochemical properties of the composite powders in the examples and counterexamples were measured by the following method.

[0081] The powder to be evaluated was sieved using a 45 µm sieve and mixed with carbon black, carbon fiber and sodium carboxymethylcellulose binder in water (2.5 wt%). The ratio used was 89 wt. parts composite powder / 1 wt. part carbon black (C65) / 2 wt. parts carbon fiber (VGCF) and 8 wt. parts carboxymethylcellulose (CMC). These components were mixed in a Pulverisette 7 planetary ball mill at 250 rpm for 30 minutes.

[0082] Copper foil cleaned with ethanol was used as current collector. A 200µm thick layer of the mixed components was coated on the copper foil. The coated copper foil was then dried at 70°C in vacuum for 45 minutes. A 1.27cm² disc was punched out of the dried coated copper foil and used as an electrode in a button cell using lithium metal as the counter electrode. The electrolyte was 1M LiPF6 dissolved in EC / DEC 1 / 1 + 2% VC + 10% FEC solvent.

[0083] All coin cells were cycled using a high precision battery tester (Maccor 4000 series) using the procedure described below, where "CC" stands for "constant current" and "CV" stands for "constant voltage".

[0084] Loop 1:

[0085] o Leave for 6 hours

[0086] oCC lithiation to 10mV at C / 10, then CV lithiation to C / 100

[0087] o Leave for 5 minutes

[0088] oCC delithiation to 1.5V at C / 10

[0089] o Leave for 5 minutes

[0090] Starting from loop 2:

[0091] oCC lithiation to 10mV at C / 2, then CV lithiation to C / 50

[0092] o Leave for 5 minutes

[0093] oCC delithiation to 1.2V at C / 2

[0094] o Leave for 5 minutes

[0095] The Coulombic efficiency (CE) of the coin cell, which is the ratio of the capacity during delithiation to the capacity during lithiation at a given cycle, is calculated for the initial cycle as well as subsequent cycles. The initial cycle is the most important cycle in terms of coulombic efficiency, because the reactions of SEI formation have a huge impact on CE. Typically, for silicon-based powders, the coulombic efficiency at the initial cycle can be as low as 80% (or even lower), which corresponds to an irreversible capacity loss of 20% for the coin cell, which is huge. The goal is to achieve a CE of at least 90% at the initial cycle.

[0096] Although the CE will typically increase to over 99% for subsequent cycles, the skilled person will appreciate that small differences in coulombic efficiency at each cycle can also have significant cumulative effects over the hundreds or thousands of charge-discharge cycles that a battery is expected to last. For example, a battery with an average CE of 99.8% with an initial capacity of 1Ah will have a remaining capacity of 0.8Ah after 100 charge-discharge cycles, which is 60% higher than a battery with an average CE of 99.5% (remaining capacity of 0.5Ah).

[0097] For cells comprising composite powders with a specific capacity of 800±20 mAh / g, the target in terms of average CE from cycle 5 to cycle 50 is to achieve at least 99.5%, preferably at least 99.55%.

[0098] Determination of number-based particle size distribution

[0099] The number-based particle size distribution of the silicon-based particles is determined via electron microscopy analysis (SEM or TEM) of cross sections of the composite powders in combination with image analysis.

[0100] To this end, cross-sections of composite powders, including multiple cross-sections of composite particles, each of which includes multiple cross-sections of silicon-based particles, are prepared according to the procedure detailed below.

[0101] 500 mg of the composite powder to be analyzed were embedded in 7 g of resin (Buehler EpoxiCure 2) consisting of a mixture of 4 parts of epoxy resin (20-3430-128) and 1 part of epoxy hardener (20-3432-032). The resulting 1'' diameter sample was dried during at least 8 hours. Then, the sample was first mechanically polished using a Struers Tegramin-30 until a maximum thickness of 5 mm was reached, and then further polished by ion beam polishing (cross section polisher Jeol SM-09010) at 6 kV for about 6 hours to obtain a polished surface. Finally a carbon coating was applied to this polished surface by 12 seconds of carbon sputtering using a Cressington 208 carbon coater to obtain a sample to be analyzed by SEM, also called a "cross section".

[0102] The prepared cross sections were then analyzed using a FEG-SEM JSM-7600F from JEOL equipped with an EDS detector Xflash 5030-127 (30 mm², 127 eV) from Bruker. The signal from this detector was processed by a Quantax 800 EDS system from Bruker.

[0103] Amplification is produced by applying a voltage of 15 kV at a working distance of a few millimeters. The image from the backscattered electrons is reported when the value is added to the image from the optical microscope.

[0104] The size of a silicon-based particle is considered to be equivalent to the maximum straight-line distance between two points on the perimeter of a discrete cross-section of the silicon-based particle.

[0105] For the purpose of illustrating, in a non-limiting manner, the determination of number-based particle size distribution of silicon-based particles, a SEM-based procedure is provided below.

[0106] 1. Take multiple SEM images of a cross section of a composite powder comprising composite particles having silicon-based particles dispersed therein.

[0107] 2. Adjust the contrast settings and brightness settings of the image to easily visualize the cross-sections of the composite particles and the silicon-based particles. Due to their different chemical compositions, the difference in brightness can easily distinguish the two types of particles.

[0108] 3. Using suitable image analysis software, select at least 1000 discrete cross-sections of silicon-based particles that do not overlap with another cross-section of silicon-based particles from one or several acquired SEM images. These discrete cross-sections of silicon-based particles can be selected from one or more cross-sections of composite particles and composite powders of silicon-based particles.

[0109] 4. For each of the at least 1000 discrete cross-sections of the silicon-based particle, use suitable image analysis software to measure the size of the discrete cross-section of the silicon-based particle.

[0110] Then, calculate the d10, d50 and d90 values ​​of the number-based particle size distribution of the powder determined using the above method.These number-based particle size distributions can be easily converted to weight- or volume-based particle size distributions via well-known mathematical formulas.

[0111] Determination of volume-based particle size distribution

[0112] The volume-based particle size distribution of the composite powders was determined using a laser diffraction particle size analyzer Malvern Mastersizer 2000. The following measurement conditions were selected: compression range; effective beam length 2.4 mm; measurement range: 300RF; 0.01 µm to 900 µm. Sample preparation and measurement were performed according to the manufacturer's instructions.

[0113] Raman spectroscopy

[0114] Raman spectroscopy analysis of the composite powders was performed using a Renishaw inVia Qontor Raman spectrometer with 532 nm laser excitation.

[0115] Perform the following steps to process the acquired spectra:

[0116] 1. Subtract the background by removing the contribution of both cosmic rays and the baseline.

[0117] 2. Using appropriate software, fit the obtained spectrum with 3 curves: D band, G band and D' band, e.g. Figure 2 In the presence of graphite particles, the spectrum of pure graphite is first acquired and its contribution to the composite powder spectrum is subtracted. In the absence of graphite particles, all D, G and D' bands must be contributions from the carbon matrix.

[0118] 3. Measurement I D / I D' ratio.

[0119] Experimental preparation of examples

[0120] Counterexample 1 (CE1) not based on the present invention

[0121] To produce the powder of Counter-Example 1, a silicon-based powder was first obtained by applying a 60kW radio frequency (RF) inductively coupled plasma (ICP) using argon as the plasma gas, into which a micron-sized silicon powder precursor was injected at a rate of about 200 g / h, thereby obtaining a prevailing (i.e., in the reaction zone) temperature above 2000 K. In this first process step, the precursor was completely vaporized. In a second process step, a 20 Nm³ / h argon flow was used as a quench gas immediately downstream of the reaction zone in order to reduce the temperature of the gas to below 1600 K, thereby causing nucleation into metallic submicron silicon powder. Finally, a passivation step was performed at a temperature of 100 ° C by adding 100 l / h of a N2 / O2 mixture containing 1 mol % of oxygen within 5 minutes.

[0122] The specific surface area (BET) of the obtained silicon powder was measured to be 82 m 2 The oxygen content of the silicon powder obtained was measured to be 7.9% by weight. The number-based particle size distribution of the silicon powder was determined to be: d10=52 nm, d50=111 nm and d90=171 nm.

[0123] Then, a dry blend was made from 100 g of the obtained silicon powder and 840 g of polyvinyl chloride (PVC) having a melting point of 160° C. The blend was heated to a temperature of 190° C. under a nitrogen stream and, after a waiting period of 60 minutes, mixed under high shear for 30 minutes by a Cowles dissolving mixer operated at 1000 rpm.

[0124] The thus obtained mixture of silicon powder in PVC was cooled to room temperature and, once solidified, pulverized and sieved on a 400 mesh screen to produce an intermediate powder 1 .

[0125] Then 20 g of the obtained intermediate powder 1 was placed in a quartz crucible in a tube furnace, heated to 900°C at a heating rate of 3°C / min, kept at this temperature for two hours, and then cooled. All of this was carried out under an argon atmosphere. In the obtained product, silicon-based particles were dispersed and embedded in a soft carbon matrix produced by the thermal decomposition of PVC.

[0126] Finally, the calcined product was ball-milled with alumina balls at 300 rpm for 1 hour, and sieved on a 325-mesh sieve to obtain a powder of Counter Example 1.

[0127] The key synthesis parameters are summarized in Table 1.

[0128] The total Si content in the powder was measured by XRF to be 39.3% by weight with an experimental error of + / - 0.3% by weight. This corresponds to a calculated value based on a weight loss of about 84% by weight of the PVC on heating and an insignificant weight loss of the other components on heating. The calculated ratio of the carbon content resulting from the carbonization of the PVC forming the matrix material to the silicon content in the powder was about 1.46. The oxygen content of the powder was measured to be 3.4% by weight. The specific surface area (BET) of the obtained powder was measured to be 3.3 m 2 / g.

[0129] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 5.4 μm, D50 equal to 15.8 μm and D90 equal to 24.6 μm.

[0130] The powder of Counterexample 1 was then analyzed by Raman spectroscopy following the procedure described previously. The peak at 1344 cm -1 The intensity of the D peak at 1610 cm -1 The ratio of the intensity of the D' peak at is 0.54. This value is reported in Table 2.

[0131] Embodiment 1 (E1) according to the present invention

[0132] The preparation method of the composite powder of Example 1 (E1) is the same as the preparation method of the composite powder of Counter Example 1 (CE1), except that the intermediate powder 1 is heated to 1000°C instead of 900°C.

[0133] The total Si content in the composite powder was measured by XRF to be 39.3 wt %. The oxygen content of the powder was measured to be 3.5 wt %. The specific surface area (BET) of the obtained powder was measured to be 3.2 m 2 / g.

[0134] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 5.2 μm, D50 equal to 16.1 μm and D90 equal to 25.2 μm.

[0135] The Raman spectrum of composite powder E1 is shown in Figure 2 As shown. The obtained -1 The intensity of the D peak at 1610 cm -1 The ratio of the intensity of the D' peak at is 1.23.

[0136] Counterexample 2 (CE2) not based on the present invention

[0137] To prepare the composite powder of Counterexample 2 (CE2), the same silicon powder as in Counterexample 1 (CE1) was used. A dry blend was made from 100 g of silicon powder and 750 g of polyvinyl chloride (PVC) having a melting point of 210° C. The blend was heated to a temperature of 240° C. under a nitrogen flow and, after a waiting period of 60 minutes, mixed under high shear for 30 minutes by a Cowles dissolving type mixer operated at 1000 rpm.

[0138] The thus obtained mixture of silicon powder in PVC was cooled to room temperature and, once solidified, pulverized and sieved on a 400 mesh screen to produce an intermediate powder 2 .

[0139] Then 20 g of the obtained intermediate powder 2 was placed in a quartz crucible in a tube furnace, heated to 900°C at a heating rate of 3°C / min, kept at this temperature for two hours, and then cooled. All of this was carried out under an argon atmosphere. In the obtained product, the silicon-based particles were dispersed and embedded in a soft carbon matrix produced by the thermal decomposition of PVC.

[0140] Finally, the calcined product was ball-milled with alumina balls at 300 rpm for 1 hour, and sieved on a 325-mesh sieve to obtain powder of Counter Example 2.

[0141] The total Si content in the powder was determined to be 39.2% by weight. This corresponds to a calculated value based on a weight loss of about 82% by weight of the PVC on heating and an insignificant weight loss of the other components on heating. The calculated ratio of the carbon content resulting from the carbonization of the PVC to the silicon content in the powder was about 1.47. The oxygen content of the powder was measured to be 3.4% by weight. The specific surface area (BET) of the obtained powder was measured to be 3.4 m 2 / g.

[0142] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 5.6 μm, D50 equal to 16.4 μm and D90 equal to 25.6 μm.

[0143] Embodiment 2 (E2) according to the present invention

[0144] The preparation method of the composite powder of Example 2 (E2) is the same as the preparation method of the composite powder of Counter Example 2 (CE2), except that the intermediate powder 2 is heated to 1000°C instead of 900°C.

[0145] The total Si content in the composite powder was measured by XRF to be 39.2 wt %. The oxygen content of the powder was measured to be 3.6 wt %. The specific surface area (BET) of the obtained powder was measured to be 3.5 m 2 / g.

[0146] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 4.9 μm, D50 equal to 15.6 μm and D90 equal to 23.8 μm.

[0147] Embodiment 3 (E3) according to the present invention

[0148] To prepare the composite powder of Example 3 (E3), the same procedure as that of the composite powder of Example 2 (E2) was used, except that 20 g of intermediate powder 2 was mixed with 26 g of graphite. The resulting mixture was placed in a quartz crucible in a tube furnace, heated to 1000°C at a heating rate of 3°C / min and held at that temperature for two hours, and then cooled. All of this was carried out under an argon atmosphere. In the obtained product, the silicon-based particles were dispersed and embedded in the soft carbon matrix produced by the thermal decomposition of PVC. The graphite particles were not embedded in the soft carbon matrix.

[0149] Finally, the calcined product was ball-milled with alumina balls at 300 rpm for 1 hour and sieved on a 325-mesh sieve to obtain a powder of Example 3.

[0150] The ratio of the carbon content resulting from carbonization of PVC to the silicon content in the composite powder E3 was about 1.47.

[0151] The total Si content in the composite powder was measured by XRF to be 17.0 wt %. The oxygen content of the powder was measured to be 1.5 wt %. The specific surface area (BET) of the obtained powder was measured to be 3.3 m 2 / g.

[0152] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 5.2 μm, D50 equal to 15.7 μm and D90 equal to 24.4 μm.

[0153] Counterexample 3 (CE3) not based on the present invention

[0154] To prepare the composite powder of Counterexample 3 (CE3), the same silicon powder as in Counterexample 1 (CE1) was used. A wet blend was made of 100 g of silicon powder and 180 g of a phenolic resin precursor (a mixture of phenol + formaldehyde) having a crosslinking temperature of 100°C and mixed under high shear for 30 minutes by a Cowles dissolving type mixer operated at 1000 rpm under a nitrogen flow. Still under a nitrogen flow, the wet blend was heated to a temperature of 200°C for 30 minutes to complete the polymerization reaction.

[0155] The thus obtained mixture of silicon powder in phenolic resin was cooled to room temperature, pulverized and sieved on a 400-mesh screen to produce an intermediate powder 3.

[0156] Then 20 g of the obtained intermediate powder 3 was placed in a quartz crucible in a tube furnace, heated to 1000°C at a heating rate of 3°C / min, kept at this temperature for two hours, and then cooled. All of this was carried out under an argon atmosphere. In contrast to the composite powder obtained previously, in the composite powder of Counter Example 3, the silicon-based particles were dispersed and embedded in the hard carbon matrix due to the thermal decomposition of the phenolic resin.

[0157] Finally, the calcined product was ball-milled with alumina balls at 300 rpm for 1 hour, and sieved on a 325-mesh sieve to obtain a powder of Counter Example 1.

[0158] The total Si content in the powder was measured by XRF to be 39.2 wt%. This corresponds to a calculated value based on a weight loss of about 25 wt% of the phenolic resin upon heating and an insignificant weight loss of the other components upon heating. The calculated ratio of the carbon content resulting from the carbonization of the phenolic resin to the silicon content in the powder was about 1.47. The oxygen content of the powder was measured to be 3.4 wt%. The specific surface area (BET) of the obtained powder was measured to be 4.2 m 2 / g.

[0159] The volume-based particle size distribution of the obtained composite particles was: D10 equal to 6.2 μm, D50 equal to 17.2 μm and D90 equal to 26.3 μm.

[0160] Table 1: Summary of synthesis parameters of composite powders E1-E3 and CE1-CE3

[0161]

[0162] Electrochemical evaluation of composite powders

[0163] The prepared composite powders were tested in button cells according to the procedure specified above. Only the composite powder E3 containing graphite reached the target capacity of 800 mAh / g ± 20 mAh / g, the specific capacity of the other powders was about 1380 mAh / g. Therefore, during the preparation of the electrode, the composite powders E1, E2, CE1, CE2 and CE3 were mixed with graphite to reach a capacity of about 800 mAh / g for the mixture "composite powder + graphite". The results obtained for the average coulombic efficiency between cycle 5 and cycle 50 are given in Table 2.

[0164] Comparing the results of the composite powders E1 to E3 according to the present invention with the results of the composite powders CE1 to CE3, it can be seen that for the composite powders containing I D / I D' The best results were obtained for cells with composite powders having ratios between 0.9 and 4.0, in particular between 1.0 and 3.0, even more in particular between 1.0 and 2.6, for possible reasons already given previously.

[0165] Table 2: Performance of button cells containing composite powders E1-E3 and CE1-CE3

[0166]

Claims

1. A composite powder for use in a negative electrode of a secondary battery, the composite powder comprising composite particles, the composite particles comprising a carbon matrix material and silicon-based particles embedded in the carbon matrix material, the composite powder having a Raman spectrum, wherein a D band and a D' band both corresponding to contributions from the carbon matrix material have a peak at 1330 cm -1 With 1360cm -1 The maximum intensity between D and at 1600cm -1 With 1620cm -1 The maximum intensity between D' , where the ratio I D / I D' At least equal to 0.9 and at most equal to 4.

0.

2. The composite powder according to claim 1, wherein the D / I D' The ratio is at least equal to 1.0 and at most equal to 3.

0.

3. The composite powder according to claim 1, wherein the D / I D' The ratio is at least equal to 1.0 and at most equal to 2.

6.

4. A composite powder according to any one of the preceding claims, wherein the carbon matrix material is soft carbon. 5 . The composite powder according to claim 1 , wherein the composite powder has a silicon content S expressed as weight percentage (wt %), wherein 10 wt % ≤ S ≤ 60 wt %. 6 . The composite powder according to claim 1 , wherein the composite powder has a carbon content C expressed as a weight percentage (wt %), wherein 30 wt %≤C≤90 wt %. 7 . The composite powder according to claim 1 , wherein the composite powder has a silicon content S and an oxygen content N, both expressed in weight percent (wt %), wherein N≦0.20 S. 8 .

8. The composite powder of any one of the preceding claims, wherein the silicon-based particles are characterized by a size distribution based on number having a d50 greater than or equal to 20 nm and less than or equal to 150 nm.

9. A composite powder according to any one of the preceding claims, wherein at least 50% of the surface of the silicon-based particles is covered by the carbon matrix material. 10 . Composite powder according to claim 1 , wherein the silicon content in the silicon-based particles is at least equal to 80% by weight.

11. The composite powder according to any one of the preceding claims, wherein the composite powder further comprises graphite and / or graphene particles, such that less than 10% of the surface of the graphite and / or graphene particles is covered by the carbon matrix material.

12. A composite powder according to any one of the preceding claims, wherein the composite powder has a maximum 2 / g and preferably at most 8m 2 / g of BET surface area.

13. The composite powder according to any one of the preceding claims, wherein the composite particles have a volume-based particle size distribution including D10, D50 and D90, wherein 1 μm≤D10≤10 μm, 5 μm≤D50≤25 μm and 10 μm≤D90≤40 μm.

14. A negative electrode comprising a composite powder according to any one of the preceding claims.

15. A secondary battery comprising the negative electrode according to claim 14.

Citation Information

Patent Citations

  • Cathode active material for lithium ion secondary battery, and cathode and battery containing the same

    CN101409345A

  • Non-aqueous electrolyte secondary battery negative electrode material, making method, lithium ion secondary battery, and electrochemical capacitor

    CN101504980A

  • Negative active material, cathode and rechargeable lithium battery including same

    CN105280891A

  • Silicon carbon composite material, fabrication method thereof, anode material and battery

    CN105742599A

  • Compositions and uses thereof

    CN109690830A